CH4 control and associated microbial process from constructed wetland (CW) by microbial fuel cells (MFC). (15th April 2020) - Zhang, Ke; Wu, Xiangling; Luo, Hongbing; Li, Xiangkun; Chen, Wei; Chen, Jia; Mo, You; Wang, Wei
Abstract: Global warming is becoming more severe. We here proposed an innovative green technique aimed at reducing the CH4 emissions from constructed wetlands (CWs) in which CH4 is controlled by microbial fuel cells (MFCs). The results of our work indicated that CH4 emissions from CWs could be controlled by operating MFC. The CH4 fluxes significantly decreased in the MFC-CW (close circuit CC) compared with the control MFC-CW (open circuit OC). The bioelectricity generation and COD removal rates also differed in the two systems. The highest power density (0.27 W m −3 ) and the lowest CH4 emissions (4.7 mg m −2  h −1 ) were observed in the CC system. The plants' effects on the performance of the MFC-CWs were also investigated. The plant species had a profound impact on the CH4 emissions and electricity production in MFC-CWs. The greatest CH4 flux (9.5 mg m −2  h −1 ) was observed from the MFC-CW planted with Typha orientalis, while the CH4 emissions from the MFC-CW planted with Cyperus alternifolius were reduced by 45%. Additional microbial processes were investigated. Quantitative real-time PCR (q-PCR) analysis indicated that the gene abundance of eubacterial 16 S rRNA, particulate methane monooxygenase ( pmo A), and methyl coenzyme M reductase ( mcr A) significantly differed for the control CW and MFC-CWs planted with different plants. In the CC systems, the mcr A genes in the anode were low, while the pmo A genes in the cathode were high. The operation of MFCs in CWs changed the exoelectrogenic and methanogenic community structures. Sequencing analysis indicated that phylotypes related to Geobacter, Bacteroides, and Desulfovibrio were specifically enriched in the CC systems. The results demonstrated that the operation of MFCs in the CWs resulted in the competition between the electrogenes and methanogenes, which resulted in distinctive microbial populations and biochemical processes that suppressed the CH4 emissions from the CWs. Graphical abstract: Image 10370 Highlights: The operation of the MFC in the CW can significantly suppress CH4 emissions. Plant species had a profound impact on the CH4 emissions and electricity production in the MFC-CWs. The abundance of the mcr A and pmo A genes differed in the open-circuit and close-circuit systems. Operation of the MFCs in the CWs resulted in distinctive microbial populations and biochemical processes.